New Evidence of Individual Level of Happiness in Indonesia: Does Easterlin Paradox Matter? - Ellytahatin Indah Sekar Putri; Dwi Prasetyani (Universitas Negeri Malang, 2021)
This study aims to estimate the determining factors of individual happiness of the head of household in Indonesia in 2014 using cross-section data from the Indonesia Family Life Survey (IFLS) batch 5 of 2014 with 5092 respondents estimated by a logit model. The Logit model was chosen due to the ordinal response variable and the dependent variable using a scale of 0 and 1. This study tested 7 independent variables using binary logistic regression. The results showed that the economic factors of employment and income had a significant effect on happiness. It implies that there was no Easterlin Paradox in Indonesia. Individual characteristic factors, comprising age, duration of education, and health showed an influence on the head of household’s level of happiness. This research found that gender and area of residence variables did not show significant results. In other words, the level of happiness of the head of household was not determined by the gender; male or female. The level of happiness of the head of household living in rural or urban areas also showed no effect.